THE RELATIONSHIP OF KNOWLEDGE, MOTIVATION AND FAMILY SUPPORT ON PROVISION OF COMPLETE BASIC IMMUNIZATION IN INFANTS 12 MONTHS AGE AT UPT PUSKESMAS BORTREM KECAMATAN BAGANSINEMBAH RAYA KABUPATEN ROKAN HILIR RIAUTAHUN 2020 - Helmi Wardah Nasution (Sean Institute, 2020)
Complete basic immunization is intended for body resistance for infants up to 12 months of age. Complete basic immunization was carried out in all parts of Indonesia, including at UPT Puskesmas Bortrem, Bagan Sinembah Raya District, Rokan Hilir Regency, Riau in 2021. The purpose of this study was to determine the relationship between knowledge, motivation and family support for providing complete basic immunization for infants aged 12 months at UPT Puskesmas Bortrem, Bagan Sinembah Raya District, Rokan Hilir Regency, Riau in 2021. This type of research uses an analytic type of research with a cross sectional design, which aims to explain the relationship of knowledge, motivation and family support to the provision of complete immunization in 12-month infants. Data analysis was done by chi square test. The population in this study were all mothers who had babies aged 0-12 months at the UPT Puskesmas Bortrem, Bagan Sinembah Raya District, Rokan Hilir Regency, Riau in 2021, as many as 30 people. The sample in this study was the entire population, namely mothers who have babies aged 0-12 months at the UPT Puskesmas Bortrem, Bagan Sinembah Raya District, Rokan Hilir Regency, Riau in 2021 as many as 30 people.The distribution of the highest frequency of research on good knowledge as many as 24 people (80.0%), low family support as many as 18 people (60.0%) and high motivation as many as 26 people (86.7%). There is a relationship between knowledge (P=0.038 ), motivation (P = 0.103), and family support (P = 0.030), by providing complete basic immunization to 12-month babies at the UPT Puskesmas Bortrem, Bagan Sinembah Raya District, Rokan Hilir Regency, Riau in 2021. It is hoped that health workers will continue to carry out health promotions in the form of counseling and information that is important for the community about giving complete basic immunizations to 12-month babies so that mothers' knowledge about giving complete basic immunizations is getting better.